LEXICO-SYNTACTICAL ANALYSIS OF STYLISTIC DEVICES IN ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA - Amirkulova Sugdiyona Yokubjon kizi (Bright Mind Publishing, 2026)
This article studies the lexico-syntactical stylistic devices used in Ernest Hemingway’s novella The Old Man and the Sea. The purpose of the research is to explain how word choice and sentence structure help to create Hemingway’s simple but meaningful writing style. The research focuses on major stylistic devices such as repetition, parallelism, understatement, enumeration, and simple sentence patterns. The study is based on qualitative analysis of selected parts of the text. The theoretical background relies on the ideas of Galperin, Leech and Short, and Simpson.
Keywords: Lexico-syntactical devices, stylistics, Ernest Hemingway, The Old Man and the Sea, repetition, simplicity, minimalism.